Range-based models in estimating value-at-risk (VaR) - Beronilla, Nikkin L.; Mapa, Dennis S. (The Philippine Review of Economics, 2008)
This paper introduces new methods of estimating Value-at-Risk (VaR) using range-based GARCH (general autoregressive conditional heteroskedasticity) models. This paper finds that range-based GARCH models are good alternatives in modeling volatility and in estimating VaR.